Biofilm in endodontics Part I. Properties and methods of study (review of the literature) (Эндодонтия Today)
About 80% of the human microbiota exists in the form of biofilms. The properties of microorganisms in the composition of biofilms differ significantly from those in planktonic suspensions. In the root canal system (RCS), the organization of microflora in biofilms has also been detected. Complex structure and individual variability of RCS in combination with unique properties of biofilm make disinfection of this system problematic. The persistence of microflora in the RCS and dentinal tubules, which continues even after qualitative clinical and radiological endodontic treatment, causes its low efficiency. In recent years, various methods for studying biofilm have been developed. The authors emphasize that the most objective of them are those that are conducted in vivo. However, it is practically impossible to implement such methods in the RCS, but methods of indirect evaluation of biofilm properties can be used. The purpose of this review is to analyze the accumulated information on the features of the biocenosis of the RCS and modern methods of studying biofilms in order to improve the effectiveness of endodontic dentistry.